2020
DOI: 10.1186/s13041-020-00607-3
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 is localized in microglia and neurons, as well as infiltrating monocytes, in the lumbar spinal cord of ALS mice

Abstract: It remains controversial whether circulating monocytes expressing CCR2 infiltrate the central nervous system (CNS) and contribute to pathogenicity of amyotrophic lateral sclerosis (ALS). A previous report used conventional immunohistochemistry to show that CCR2 is exclusively expressed by astrocytes, but not infiltrating monocytes/ microglia or neurons, in the spinal cords of ALS model mice. In this study, we assessed the cellular distribution of CCR2 in the CNS of ALS mice using CCR2-reporter mice (Ccr2 rfp/+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Interestingly, cenicriviroc prevented nerve injury-induced upregulation of CCR2 in the spinal cord and CCR5 in the DRG. These chemokine receptors are expressed in both neuronal (28,29) and non-neuronal (2,26,(30)(31)(32)(33)(34)(35) cells, such as microglia, astrocytes, macrophages, satellite cells, and infiltrating T lymphocytes. Here, we demonstrated that cenicriviroc might act as a microglia/macrophage and satellite cell activation inhibitor; in contrast, it did not influence the spinal level of the astrocyte activation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cenicriviroc prevented nerve injury-induced upregulation of CCR2 in the spinal cord and CCR5 in the DRG. These chemokine receptors are expressed in both neuronal (28,29) and non-neuronal (2,26,(30)(31)(32)(33)(34)(35) cells, such as microglia, astrocytes, macrophages, satellite cells, and infiltrating T lymphocytes. Here, we demonstrated that cenicriviroc might act as a microglia/macrophage and satellite cell activation inhibitor; in contrast, it did not influence the spinal level of the astrocyte activation.…”
Section: Discussionmentioning
confidence: 99%
“…Several ongoing clinical trials have depicted great progress in GBM treatment with ICI (56,68) and CAR-T therapy (69,70). However, a large number of patients still do not respond to these treatments ( 71 (72)(73)(74)(75). It has been reported that astrocytes are the main cell types that express CCR2 in normal brain tissues, which helps maintain certain infiltration of macrophages and microglia to execute an innate immune response, and maintain homeostasis in the CNS environment (73,76).…”
Section: Novel Therapeutics Based On Tam/m Regulation For Enhancing Effector T Cells In Glioblastomamentioning
confidence: 99%
“…However, a large number of patients still do not respond to these treatments ( 71 (72)(73)(74)(75). It has been reported that astrocytes are the main cell types that express CCR2 in normal brain tissues, which helps maintain certain infiltration of macrophages and microglia to execute an innate immune response, and maintain homeostasis in the CNS environment (73,76). GBM cells have been reported to express the CCR2 ligand to raise microglia (16), which likely enhances GBM malignancy by creating an antiimmune environment.…”
Section: Novel Therapeutics Based On Tam/m Regulation For Enhancing Effector T Cells In Glioblastomamentioning
confidence: 99%
“…Frozen sections (20 µm thick) of mouse lumbar spinal cords were prepared using a previously described method [20,24] at each disease stage (early stage, 12 weeks; middle stage, 16 weeks; late stage, 20 weeks; end stage, 24 weeks). The sections were permeabilized with 1% Triton-X-100 in PBS for 30 min, blocked with 10% FBS for 1 h, and incubated overnight with rabbit anti-mouse Iba1 polyclonal antibodies (1:300; Wako, Tokyo, Japan), mouse anti-NeuN monoclonal antibody (CI: A60, 1:500; Chemicon, Temecula, CA, USA), rabbit anti-mouse GFAP polyclonal antibodies (1:1000; Dako, Glostrup, Denmark), and rat anti-CD68 monoclonal antibody (CI: FA-11, 1:500; Bio-Rad, Hercules, CA, USA), followed by incubation with Alexa Fluor 488 or Alexa Fluor 546-conjugated secondary antibodies (Life Technologies).…”
Section: Histological Analysismentioning
confidence: 99%
“…The sections were permeabilized with 1% Triton-X-100 in PBS for 30 min, blocked with 10% FBS for 1 h, and incubated overnight with rabbit anti-mouse Iba1 polyclonal antibodies (1:300; Wako, Tokyo, Japan), mouse anti-NeuN monoclonal antibody (CI: A60, 1:500; Chemicon, Temecula, CA, USA), rabbit anti-mouse GFAP polyclonal antibodies (1:1000; Dako, Glostrup, Denmark), and rat anti-CD68 monoclonal antibody (CI: FA-11, 1:500; Bio-Rad, Hercules, CA, USA), followed by incubation with Alexa Fluor 488 or Alexa Fluor 546-conjugated secondary antibodies (Life Technologies). The stained cells were analyzed in six random fields per section using a deconvolution fluorescence microscope system (BZ-X800; Keyence, Osaka, Japan) as described previously [20,24]. Data were collected from six sections per mouse and four mice per group.…”
Section: Histological Analysismentioning
confidence: 99%